2011
DOI: 10.1126/scitranslmed.3003062
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism for a Gateway Drug: Epigenetic Changes Initiated by Nicotine Prime Gene Expression by Cocaine

Abstract: In human populations, cigarettes and alcohol generally serve as gateway drugs, which people use first before progressing to marijuana, cocaine or other illicit substances. To understand the biological basis of the gateway sequence of drug use, we developed an animal model in mice and focused on the effects of nicotine on subsequent responses to cocaine. We found that pretreatment of mice with nicotine increased the response to cocaine as assessed by both addiction-related behaviors and synaptic plasticity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
231
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(249 citation statements)
references
References 33 publications
13
231
2
3
Order By: Relevance
“…Furthermore, the involvement of a6b2* nAChRs was confirmed by the blockade of cocaine CPP with a-conotoxin MII [H9A; L15A] given i.c.v. These results are not surprising as previous studies have shown that nicotinic agonists and antagonists modulate cocaine reward, reinforcement, and sensitization (Champtiaux et al, 2006;Horger et al, 1992;Levine et al, 2011;Reid et al, 1998;Reid et al, 1999;Zachariou et al, 2001;Zanetti et al, 2007). Our results expand on a previous study implicating a role for b2 in cocaine place preference (Zachariou et al, 2001) by suggesting that a6 is the subunit co-expressed in the nicotinic subtype that is mediating the reward like effects of cocaine.…”
Section: A6* Nachrs Subtypes In Nicotine Cppsupporting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, the involvement of a6b2* nAChRs was confirmed by the blockade of cocaine CPP with a-conotoxin MII [H9A; L15A] given i.c.v. These results are not surprising as previous studies have shown that nicotinic agonists and antagonists modulate cocaine reward, reinforcement, and sensitization (Champtiaux et al, 2006;Horger et al, 1992;Levine et al, 2011;Reid et al, 1998;Reid et al, 1999;Zachariou et al, 2001;Zanetti et al, 2007). Our results expand on a previous study implicating a role for b2 in cocaine place preference (Zachariou et al, 2001) by suggesting that a6 is the subunit co-expressed in the nicotinic subtype that is mediating the reward like effects of cocaine.…”
Section: A6* Nachrs Subtypes In Nicotine Cppsupporting
confidence: 77%
“…For example, Horger et al (1992) observed increased cocaine self-administration by rats that were preexposed to nicotine. Levine et al (2011) recently observed that nicotine pretreatment increased cocaine locomotor sensitization and conditioned place preference (CPP) in mice. Similarly, the nonselective nicotinic antagonist mecamylamine decreased cocaine self-administration in rats (Levin et al, 2000;Blokhina et al, 2005) and reduced cue-induced cocaine craving in cocaine-dependent and cigarette smoking humans (Reid et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This period of life is a very sensitive age in which the negative affective state associated with nicotine withdrawal is reduced while the rewarding action of nicotine is enhanced compared to adults (Carcoba et al, 2014;Dickson et al, 2014;Dickson et al, 2011;Hutchison and Riley, 2008;Lee et al, 2015;McQuown et al, 2009;Natividad et al, 2012;Natividad et al, 2010;Natividad et al, 2013;O'Dell et al, 2004;O'Dell et al, 2006;O'Dell et al, 2007;Shram et al, 2008;Torres et al, 2008;Wilmouth and Spear, 2004), making adolescents a vulnerable target to nicotine use and abuse as well as for use of other addictive drugs during adulthood. Consistent with this notion, previous studies have shown that nicotine exposure during adolescence can prime the use and abuse of cocaine, alcohol, and other addictive substances (Bechtholt and Mark, 2002;DiFranza and Guerrera, 1990;Horger et al, 1992;Hutchison and Riley, 2008;Kandel and Kandel, 2015;Kandel and Kandel, 2014;Kelley and Rowan, 2004;Kouri et al, 2001;Levine et al, 2011;Li et al, 2014;McQuown et al, 2007;McQuown et al, 2009;Meliska et al, 1995;Natividad et al, 2010;Rinker et al, 2011;Rosenberg, 2014;Schindler et al, 2012;Schneider et al, 2012). There is also evidence showing that about 90% of regular smokers start using tobacco at an early age, and that early onset smoking carries a major risk for the development of addiction to other drugs of abuse (Rimm et al, 1995).…”
Section: Introductionmentioning
confidence: 78%
“…Many studies have reported that nicotine may serve as a gateway drug for cocaine and other illicit drugs (Dickson et al, 2014;Dickson et al, 2011;Levine et al, 2011;Li et al, 2014;McQuown et al, 2007;Orsini et al, 2008). However, there is limited information on the effect of nicotine treatment on the rewarding action of cocaine if nicotine is administered during adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation